Graphite negative electrode material and preparation method and application thereof
By preparing graphite negative electrode materials with suitable pore volume and specific surface area, and using material defects to construct lithium ion deintercalation paths, the problem of insufficient fast charging performance of existing graphite negative electrode materials is solved, and the excellent fast charging performance of lithium ion batteries is achieved.
Patent Information
- Application Number
- CN202311171317.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-14
AI Technical Summary
The fast charging performance of existing graphite anode materials in lithium-ion batteries is insufficient, which affects the application efficiency of the battery.
By mixing the coke-like material with asphalt, granulating and graphitizing it, graphite negative electrode material with a pore volume of ≤0.05 cm3/g and a specific surface area of ≤2m2/g was prepared, and the defects of the material were added to build a shorter and wider lithium ion deintercalation path.
The rapid embedding and disengagement of lithium ions is improved, and the fast charging performance of lithium ion batteries is significantly improved, so that the gram capacity ratio of the battery at 2C and 0.2C currents reaches more than 30%.
Smart Images

Figure BDA0004444010940000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphite negative electrode materials, and in particular to a graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] As the mainstream negative electrode material for lithium-ion batteries, graphite negative electrode materials have received extensive attention, and fast charging performance is one of the key performance factors affecting their application. The fast charging performance of lithium-ion batteries is affected by the channels for lithium ion deintercalation in graphite negative electrode materials. The shorter and wider the channels for lithium ion deintercalation, the easier it is for the material to quickly embed and deintercalate lithium ions, and the better the corresponding fast charging performance. Therefore, it is extremely important to obtain a graphite negative electrode material with good fast charging performance. Summary of the invention
[0003] The purpose of the present invention is to provide a graphite negative electrode material and a preparation method and application thereof in order to overcome the defects of the above-mentioned prior art.
[0004] The present invention solves the technical problem by adopting the following technical solutions.
[0005] In a first aspect, the present invention provides a graphite negative electrode material, wherein the graphite negative electrode material has defects and the pore volume of the graphite negative electrode material is ≤0.05cm 3 / g, specific surface area ≤2m 2 / g, the adsorption amount Q of the dye satisfies: 0.1≤Q≤1mg / g; the adsorption amount is the saturated adsorption amount of the dye by graphite at 25°C.
[0006] The graphite negative electrode material of the present invention has a lower pore volume and specific surface area, eliminating the influence of pore adsorption on the amount of dye adsorption. There are certain defects on the surface of the graphite negative electrode material. The presence of defects is conducive to the construction of a shorter and wider lithium ion deintercalation path. The shorter and wider the lithium ion deintercalation channel is, the easier it is for lithium ions to be quickly intercalated and removed, that is, the corresponding fast charging performance will be better. The inventors found that the presence of lattice defects will lead to an uneven distribution of electron clouds on the surface of the material, thereby placing the material in a polar state, and this polar state will also interact with the organic dye to form adsorption of the dye.
[0007] The lithium ion battery using graphite with a dye adsorption amount of 0.1≤Q≤1mg / g as the negative electrode material has a gram capacity ratio of more than 30% at currents of 2C and 0.2C, and the secondary battery provided by the present invention has excellent fast charging performance.
[0008] Preferably, the adsorption amount of the dye by the graphite negative electrode material is 0.2≤Q≤0.4 mg / g.
[0009] Preferably, the pore volume of the graphite negative electrode material is ≤0.04 cm3 / g; specific surface area ≤1.5m 2 / g.
[0010] Preferably, the graphite negative electrode material is artificial graphite.
[0011] Preferably, the dye is methyl orange or methylene blue.
[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned graphite negative electrode material, comprising: mixing a charred material with asphalt, granulating, and graphitizing; the ash content of the charred material is ≤0.5%, and the S content is 2%≤≤5%.
[0013] Preferably, the content of asphalt is ≤15%;
[0014] Preferably, the coke-like material is green coke or semi-forged coke.
[0015] Preferably, the raw material of the coke-like material is petroleum coke, needle coke or asphalt coke.
[0016] The preparation steps of the semi-calcined coke include: treating the original petroleum coke, needle coke and pitch coke materials to obtain coke particles with a D50 of 0.1 to 5 mm, and then treating them at a temperature of 500 to 900° C. for 2 to 6 hours;
[0017] In the semi-calcined polarized structure, the sum of the long and thin fiber structure and the wide-area structure accounts for 55-99%, and 1%≤volatile matter<5%.
[0018] Preferably, the method for preparing the graphite negative electrode material meets the following conditions:
[0019] (1) The granulation temperature is 300-650° C. and the granulation time is 4-12 hours;
[0020] (2) The temperature of the graphitization treatment is 2500-3500°C, and the graphitization time is 1-8h.
[0021] (3) The granulation and graphitization steps are carried out under an inert atmosphere; the inert atmosphere is one or more of nitrogen, argon, and helium.
[0022] In the present invention, a graphite negative electrode material is obtained by mixing a coke-like material with asphalt, granulating, and graphitizing. The coke-like raw material is preferably: raw coke or semi-calcined coke with an ash content ≤0.5% and an S content ≤2% ≤5%. The S in the coke will overflow during the graphitization process to produce pores, which provide channels for the rapid transmission of lithium ions and improve the fast charging performance; the ash is mainly composed of metal impurities, and some transition metals have catalytic graphitization, causing multi-point nucleation of graphite crystals and excessive growth, resulting in more defects, which is beneficial to the rapid transmission of lithium ions. Therefore, the present invention controls the ash content and S content of the coke-like raw material within the above range, so that the graphite negative electrode material has certain defects and the pore volume is ≤0.05cm 3 / g, specific surface area ≤2m 2 / g, which eliminates the influence of pore adsorption on the dye adsorption amount to a certain extent, so that the dye adsorption amount of the graphite negative electrode material meets 0.1≤Q≤1mg / g. The gram capacity ratio of the lithium ion battery with the graphite as the negative electrode material at the current of 2C and 0.2C is above 30%, and has excellent fast charging performance.
[0023] In a third aspect, the present invention provides a negative electrode plate, comprising the above-mentioned graphite negative electrode material.
[0024] The present invention provides a negative electrode sheet. The preparation method of the negative electrode sheet is as follows: a graphite negative electrode material and optional conductive agents (such as carbon black and other carbon materials), a binder (such as SBR), a thickener and dispersant (such as CMC) and other optional additives (such as PTC thermistor materials) are mixed together and dispersed in a solvent (such as deionized water), stirred evenly and coated on at least one surface of a negative electrode current collector, and dried to obtain a negative electrode sheet containing a negative electrode film.
[0025] In a fourth aspect, the present invention provides a secondary battery comprising the above-mentioned negative electrode plate.
[0026] The preparation method of the secondary battery is as follows: the secondary battery is mainly composed of a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet contains the graphite negative electrode material provided in the embodiment of the present invention, and the negative electrode sheet is prepared by the aforementioned preparation method. The positive and negative electrode sheets are immersed in the electrolyte, and the active ions move between the positive and negative electrodes with the electrolyte as the medium to realize the charging and discharging of the battery. In order to avoid short circuit between the positive and negative electrodes through the electrolyte, an isolation membrane is required to separate the positive and negative electrodes. The structure and preparation method of the secondary battery of the present invention are well known in themselves. In the battery, the specific types and compositions of the positive electrode material, the separator and the electrolyte are not subject to specific restrictions and can be selected according to actual needs.
[0027] The present invention has the following beneficial effects:
[0028] The present invention provides a graphite negative electrode material and a preparation method and application thereof. The graphite negative electrode material has defects, and the pore volume is ≤0.05cm 3 / g, specific surface area ≤2m 2 / g, and the dye adsorption amount Q satisfies 0.1≤Q≤1mg / g. The gram capacity ratio of the lithium ion battery with graphite as the negative electrode material at the current of 2C and 0.2C is above 30%. The secondary battery provided by the present invention has excellent fast charging performance. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0030] A graphite negative electrode material, a preparation method and an application thereof provided in an embodiment of the present invention are specifically described below.
[0031] Example 1
[0032] This embodiment provides a negative electrode material for a lithium-ion battery, including graphite 1. The pore volume, specific surface area and adsorption amount of the dye of graphite 1 are shown in Table 1.
[0033] The present embodiment provides a method for preparing a graphite negative electrode material, comprising: mixing a 10.5 μm petroleum coke raw material having an ash content of 0.5% and an S content of 5% with an asphalt content of 15% by mass, stirring with VC (without heating), granulating for 5 hours in a vertical reactor with an inert gas, the granulation temperature being 650° C., and then graphitizing at 3500° C. for 2 hours to obtain graphite 1.
[0034] The adsorption amount was obtained by the following method:
[0035] 1. Prepare 0 mg / L, 1.5 mg / L, 3 mg / L, 4.5 mg / L, 6 mg / L, 7.5 mg / L, and 9 mg / L methyl orange standard solutions, and use an ultraviolet spectrophotometer to test the absorbance of the standard solutions at the maximum absorption wavelength of the dye (the maximum absorption wavelength of methyl orange is 464 nm) at a temperature of 25°C, and determine the standard curve by fitting according to the Lambert-Beer law;
[0036] 2. Take 0.1g of graphite negative electrode material and the initial concentration C 0 The 3 mg / L methyl orange solution was adsorbed in a water constant temperature oscillator with an oscillation frequency of 150 r / min. The oscillation was stopped after the adsorption was completed.
[0037] 3. Filter, test the absorbance of the clear solution, and calculate the concentration C of methyl orange after adsorption based on the standard curve.
[0038] 4. Calculate the adsorption amount Q according to the following formula:
[0039] Q=(C 0 -C)V / m, where C 0 is the initial concentration of the dye, in mg / L, C is the concentration of the dye after adsorption, in mg / L, V is the volume of the dye, in L, and m is the mass of the graphite negative electrode material, in g.
[0040] Example 2
[0041] This embodiment provides a negative electrode material for a lithium-ion battery, including graphite 2. The pore volume, specific surface area and adsorption amount of the graphite 2 for dye are shown in Table 1.
[0042] A method for preparing a graphite negative electrode material comprises the following steps: crushing a needle coke raw material with an ash content of 0.4% and an S content of 4% to 11.2 μm, adding 10% asphalt, stirring with VC (without heating), granulating in a vertical reactor with an inert gas at a granulation temperature of 650° C., and then graphitizing at 3500° C. for 2 hours to obtain a graphite negative electrode material.
[0043] The method for obtaining the adsorption amount is the same as that in Example 1.
[0044] Example 3
[0045] This embodiment provides a negative electrode material for a lithium-ion battery, including graphite 3. The pore volume, specific surface area and adsorption amount of the graphite 3 for dye are shown in Table 1.
[0046] A method for preparing a graphite negative electrode material comprises the following steps: crushing a needle coke semi-calcined raw material with an ash content of 0.3% and an S content of 3.5% to 11.4 μm, adding 10% asphalt, stirring with VC (without heating), granulating in a vertical reactor with an inert gas at a granulation temperature of 650° C., and then graphitizing at 3500° C. for 2 hours to obtain a graphite negative electrode material.
[0047] The method for obtaining the adsorption amount is the same as that in Example 1.
[0048] Example 4
[0049] This embodiment provides a negative electrode material for a lithium-ion battery, including graphite 4. The pore volume, specific surface area and adsorption amount of the graphite 4 for dye are shown in Table 1.
[0050] A method for preparing a graphite negative electrode material comprises the following steps: crushing a needle coke raw material with an ash content of 0.25% and an S content of 2.5% to 12.5 μm, adding 4% asphalt, stirring with VC (without heating), granulating in a vertical reactor with an inert gas at a granulation temperature of 650° C., and then graphitizing at 3500° C. for 2 hours to obtain a graphite negative electrode material.
[0051] The method for obtaining the adsorption amount is the same as that in Example 1.
[0052] Example 5
[0053] This embodiment provides a negative electrode material for a lithium-ion battery, including graphite 5. The pore volume, specific surface area and adsorption amount of the graphite 5 for dye are shown in Table 1.
[0054] A method for preparing a graphite negative electrode material comprises the following steps: crushing a petroleum coke raw material with an ash content of 0.2% and an S content of 2% to 10.7 μm, adding 4% asphalt, stirring with VC (without heating), granulating in a vertical reactor with an inert gas at a granulation temperature of 650° C., and then graphitizing at 3500° C. for 2 hours to obtain a graphite negative electrode material.
[0055] The method for obtaining the adsorption amount is the same as that in Example 1.
[0056] Testing method for 2C / 0.2C fast charging performance: The graphite in the present invention is used as the negative electrode material and assembled into a button battery. In a constant temperature box at 25°C, the battery is left to stand for 6 hours, then discharged at 0.05C constant current to 5mV; left for 10 minutes; discharged at 50μA constant current to 5mV; left for 10 minutes; discharged at 10μA constant current to 5mV; left for 10 minutes; charged at 0.1C constant current to 2V; the above cycle is repeated for 2 weeks; then the battery is discharged at 0.2C constant current and constant voltage with a cut-off current of 0.005C; left for 10 minutes; charged at 0.2C constant current; left for 10 minutes; discharged at 2C constant current; finally, the ratio of the capacity at 2C and 0.2C is used to evaluate the difference in the fast charging performance of the material.
[0057] Table 1 Specific surface area, total pore volume, adsorption capacity and fast charging performance of lithium-ion batteries in the examples
[0058]
[0059]
[0060] As shown in Table 1, the pore volume is ≤ 0.05 cm 3 / g, specific surface area ≤2m 2 / g, the adsorption amount Q of the dye satisfies: 0.1≤Q≤1mg / g of graphite as the negative electrode material of lithium-ion battery, the gram capacity ratio data at currents of 2C and 0.2C are both greater than 30%, and has good fast charging performance;
[0061] Use pore volume ≤ 0.05cm 3 / g, specific surface area ≤2m 2 / g, and the adsorption amount Q of the dye satisfies: 0.1≤Q≤1mg / g of graphite as the negative electrode material of lithium-ion battery, and the gram capacity ratio data at currents of 2C and 0.2C are both greater than 32%.
[0062] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A graphite negative electrode material, characterized in that: The graphite negative electrode material has defects, and the pore volume of the graphite negative electrode material is ≤0.05cm 3 / g, specific surface area ≤2m 2 / g, the adsorption amount Q of the dye satisfies: 0.1≤Q≤1mg / g; The adsorption amount is the saturated adsorption amount of the dye by graphite at 25°C.
2. The graphite negative electrode material according to claim 1, characterized in that The adsorption capacity of the graphite negative electrode material for the dye is 0.2≤Q≤0.4mg / g; preferably, the pore volume of the graphite negative electrode material is ≤0.04cm 3 / g, specific surface area ≤1.5m 2 / g.
3. The graphite negative electrode material according to claim 1 or 2, characterized in that: The graphite negative electrode material is artificial graphite.
4. The graphite negative electrode material according to any one of claims 1 to 3, characterized in that The dye is methyl orange or methylene blue.
5. A method for preparing a graphite negative electrode material according to any one of claims 1 to 4, characterized in that: include: The charred material is mixed with asphalt, granulated, and graphitized; the ash content of the charred material is ≤0.5%, and the S content is ≤2%≤5%.
6. The method for preparing a graphite negative electrode material according to claim 5, characterized in that: The content of the asphalt is ≤15%.
7. The method for preparing a graphite negative electrode material according to claim 5, characterized in that: The coke-like material is raw coke or semi-forged coke; Preferably, the raw material of the coke-like material is petroleum coke, needle coke or asphalt coke.
8. The method for preparing a graphite negative electrode material according to claim 5, characterized in that: The preparation method of the graphite negative electrode material meets the following conditions: (1) The granulation temperature is 300-650° C. and the granulation time is 4-12 hours; (2) The temperature of the graphitization treatment is 2500-3500°C, and the graphitization time is 1- 8h; (3) The granulation and graphitization steps are performed under an inert atmosphere.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the graphite negative electrode material according to any one of claims 1 to 4 or the graphite negative electrode material prepared by the preparation method according to any one of claims 5 to 8.
10. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet according to claim 9.